Implikasi Hukum Pidana Penyalahgunaan Data Pribadi Kasus Dharma Pongrekun Pilkada Jakarta Berdasarkan Teori Penegakan Hukum - Endah Astuti; Ade Maman Suherman; Tri Setiady (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the legal implications of personal data misuse during the 2024 Jakarta gubernatorial election involving Dharma Pongrekun. The research highlights systemic challenges in safeguarding data privacy in Indonesia, particularly in electoral contexts. Employing a normative juridical method, the study focuses on the application of the Personal Data Protection Law (UU PDP) and its enforcement mechanisms. Findings reveal that unauthorized use of voter data, such as identity theft, poses a severe threat to electoral integrity and public trust. The lack of coordination among regulatory bodies, combined with insufficient public awareness, exacerbates the issue. The study emphasizes the urgent need for comprehensive reforms, including stricter law enforcement, increased institutional accountability, and improved technological infrastructure. Furthermore, the findings advocate for public education on the importance of data privacy, especially in democratic processes. These measures aim to bolster electoral transparency, protect individual rights, and ensure justice in cases of data misuse. The research provides a valuable contribution to discussions on data protection and electoral governance in Indonesia. Strengthening the enforcement of the UU PDP is crucial to addressing these challenges and fostering trust in both the legal system and democratic processes.